Animal Models of Dysregulated Cardiac Metabolism. Issue 12 (10th June 2022) - Bugger, Heiko; Byrne, Nikole J.; Abel, E. Dale
Abstract : As a muscular pump that contracts incessantly throughout life, the heart must constantly generate cellular energy to support contractile function and fuel ionic pumps to maintain electrical homeostasis. Thus, mitochondrial metabolism of multiple metabolic substrates such as fatty acids, glucose, ketones, and lactate is essential to ensuring an uninterrupted supply of ATP. Multiple metabolic pathways converge to maintain myocardial energy homeostasis. The regulation of these cardiac metabolic pathways has been intensely studied for many decades. Rapid adaptation of these pathways is essential for mediating the myocardial adaptation to stress, and dysregulation of these pathways contributes to myocardial pathophysiology as occurs in heart failure and in metabolic disorders such as diabetes. The regulation of these pathways reflects the complex interactions of cell-specific regulatory pathways, neurohumoral signals, and changes in substrate availability in the circulation. Significant advances have been made in the ability to study metabolic regulation in the heart, and animal models have played a central role in contributing to this knowledge. This review will summarize metabolic pathways in the heart and describe their contribution to maintaining myocardial contractile function in health and disease. The review will summarize lessons learned from animal models with altered systemic metabolism and those in which specific metabolic regulatory pathways have been genetically altered within the heart. The relationship between intrinsic and extrinsic regulators of cardiac metabolism and the pathophysiology of heart failure and how these have been informed by animal models will be discussed.